Emergence and Migration of a Nearshore Bar: Sediment Flux and Morphological Change on a Multi-Barred Beach in the Great Lakes - Greenwood, Brian; Permanand-Schwartz, Allana; Houser, Christopher (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractBurley Beach (southeastern Lake Huron) exhibits a multi-barred shoreface, the long-term equilibrium morphology characteristic of many low angle, sandy beaches in the Canadian Great Lakes. During a single major storm, a new bar emerged 50-60 m offshore as an irregular trough-crest form, through differential erosion of an existing shore terrace. Emergence, bar growth and offshore migration were associated with: (a) an overall negative sediment balance in the inner surf zone initially (‑2.30 m3>/m beach width), but with a large positive sediment balance (+5.10 m3/m) subsequent to the storm peak and during the storm decay; (b) progradation of the beach step to produce a new shore terrace; and (c) offshore migration of the two outer bars to provide the accommodation space necessary for the new bar. The primary transport mechanisms accounting for emergence of the new bar, its growth and migration were: (a) the mean cross-shore currents (undertow), which always transported suspended sediment offshore; and (b) the onshore transport of suspended sediment by incident gravity wave frequencies early in the storm and subsequently by infragravity waves (at the storm peak and the decay period). The longshore transport of sediment was significant in terms of the gross transport, although the net result was only a small transport to the south-west (historic littoral transport direction). It did not cause bar initiation, but it may have supplied some of the sediment for bar growth. The primary mechanism for bar initiation and growth was the cross-shore displacement of sediment by wave-driven (oscillatory) transport and cross-shore mean currents (undertow).